Quantitative Optical Coherence Elastography for Robust Stiffness Assessment - Liu, Xuan (Appl Sci (Basel), 2018)
We demonstrated the capability of quantitative optical coherence elastography (qOCE) for robust assessment of material stiffness under different boundary conditions using the reaction force and displacement field established in the sample.